ORAL MICROBIOTA AND ORAL HEALTH CONNECTION - Dana Gabriela Budală; Zenaida Surlari; Maria Bolat; Elena Raluca Baciu; Mihaela Monica Scutariu; Dragoș Ioan Virvescu (Romanian Dental Association for Education, 2021)
Introduction: Oral involuntary changes in total edentulous age often lead to therapeutic difficulties and complications that may interfere with or influence prosthetic iatrogenesis. Purpose: The aim of this clinical study was to identify bone complications of denture bearing areas and to establish their frequency in the group of complete edentulous patients. Material and methods: The study group consisted of 130 patients, 60 males and 70 females,complete edentulous aged between 30 and> 80 years. All data obtained from study group patients were centralized and statistically analyzed. Results and discussions: Of the 130 patients, after clinical examination it was revealed the presence of 86 hyperostotic tuberosities. A total of 49 patients (37.69%) were diagnosed with a maxillary tori and the existence of mandibular torus was found in the case of 26 patients (20%). Conclusions: Careful investigation of the general and local condition, is a particularly valuable tool in detecting bone complications